Software Engineering / A Practitioner's Approach (Mcgraw Hill Book Company Pressman Roger, 1992)
24 chapters that address every important topic in what some have called ''the engineering discipline of the 1990s''. Preface, Software - The Process and Its Management, System and Software Requirements Analysis, The Design and Implementation of Software, Ensuring and Verifying and Maintaining Software Integrity, The Role of Automation, Index.